PEMANFAATAN SEKAM PADI TERAMONIASI SERTA TERBIOFERMENTASI DALAM RANSUM DISUPLEMENTASI DAUN SIRIH (Piper beetle L.) TERHADAP PENAMPILAN ITIK BALI BETINA FASE PERTUMBUHAN - I. B. G., PARTAMA; YADNYA, T. G. B.; TRISNADEWI, A. A. A. S. (Majalah Ilmiah Peternakan, 2018)
An experiment was carried out to study the effect on the use of amoniated and biofermented rice hull in diets and Piper beele leaf supplemented on performance of male bali ducks in growth phase. A completely randomized design (CRD) was used with five treatments, such as diet without rice hull (A), diets containing 10% rice hull (B), diets containing 10% amoniated and biofermented rice hull (C), diets containing 10% rice hull and Piper beetle leaf (D), diets containing 10% amoniated and biofermented rice hull and Piper beetle leaf (E). There were five female ducks with four replications in each treatment. The variables observed were diets consumption, degestible of diets, final body weight, body weight gain, and feed convertion ratio (FCR). It showed that 10% amoniated and biofermented of rice hull fed to the ducks did not give effect to diets consumption (P>0,05). In contrast, feed digestibility, final body weight, body weight gain were significantly higher (P<0.05). Moreover, the FCR was lower compared to other treatments. It can be concluded that amoniated and biofermented of rice hull, supplemented Piper beetle leaf can improve performance of male bali duck in growth phase compared to other treatments.